Binary White Dwarfs in the Galactic Halo. Issue Volume 9:Issue S298(2013) (6th January 2014) - van Oirschot, Pim; Nelemans, Gijs; Helmi, Amina; Starkenburg, Else; Pols, Onno; Brown, Anthony G.A.
Abstract : We use the stellar population synthesis code SeBa (Portegies Zwart & Verbunt (1996), Toonen, Nelemans & Portegies Zwart (2012)) to study the halo white dwarf population. Here we assume a Kroupa initial mass function and compare 4 models, varying two parameters: the star formation (SF) history of the halo (either continuous SF during 2.5 Gyr, which started 13.2 Gyr ago, or a SF burst during 360 Myr, which started 12.9 Gyr ago – see the left panel of the figure) and the binary fraction of the halo (either 100% single stars, or 100% binaries). White dwarf cooling models (Althaus et al . (2009) and Renedo et al . (2010)) allow us to plot the halo white dwarf luminosity function for these 4 models, as is done in the right panel of the figure. Combined with an assumption about the density distribution of halo stars, we will study which of these white dwarfs Gaia can see, and what that can tell us about the initial parameter distributions in the halo. In the near future, we plan to use the Munich-Groningen semi-analytical galaxy formation model (Starkenburg et al . (2013)), to obtain key ingredients for the population synthesis modeling, such as a realistic star formation history (see the left panel of the figure).